Efficacy of dupilumab in moderate and severe atopic dermatitis - Stephan Weidinger; Eric L. Simpson; Jonathan I. Silverberg; Jochen Schmitt; Yael A. Leshem; Norito Katoh; Zhen Chen; Haixin Zhang; Brad Shumel; Ashish Bansal; Jingdong Chao; Yufang Lu; et al. (Wiley, 2023)
Abstract Background Treatment responses may differ between patients with severe versus moderate atopic dermatitis (AD). Objectives To assess dupilumab response by baseline AD severity in adolescent and adult patients with moderate‐to‐severe AD. Methods We assessed dupilumab response by baseline AD severity in 1719 patients aged ≥12 years with moderate‐to‐severe AD from five randomized, double‐blind, placebo‐controlled trials. Patients received subcutaneous placebo or dupilumab as monotherapy (300 mg [adults, adolescents] or 200 mg [adolescents] every 2 weeks; 16 weeks), or with concomitant topical corticosteroids (TCS) (adults; 16/52 weeks). Patients were stratified by baseline Investigator's Global Assessment (IGA) score (3 [moderate]/4 [severe]). Results Dupilumab‐treated patients with moderate AD had numerically higher absolute proportions of patients achieving IGA 0/1 (clear/almost clear) than those with severe AD; risk differences (dupilumab vs. placebo) were 18.9-35.5 for moderate AD and 16.4-34.2 for severe AD. For all other endpoints assessed, no meaningful differences or consistent response patterns between moderate and severe subgroups were observed. Conclusions Dupilumab with or without TCS demonstrated similar efficacy in patients with moderate or severe AD.